Not Two Sides of the Same Coin: A Qualitative Comparative Analysis of Post-Treatment Abstinence and Relapse - Pars E; Hirzalla F; VanDerNagel JEL; Dijkstra BAG; Schellekens AFA (Dove Medical Press, 2024)
Esther Pars,1- 4 Fadi Hirzalla,5 Joanne EL VanDerNagel,2,3,6,7 Boukje AG Dijkstra,2,8,9 Arnt FA Schellekens1,2 1Department of Psychiatry, Radboud University Medical Center, Nijmegen, the Netherlands; 2Nijmegen Institute for Scientist-Practitioners in Addiction (NISPA), Nijmegen, the Netherlands; 3Department of Human Media Interaction, University of Twente, Enschede, the Netherlands; 4Salvation Army, Ugchelen, The Netherlands; 5Department of Public Administration and Sociology, Erasmus University, Rotterdam, the Netherlands; 6Tactus Addiction Care, Deventer, the Netherlands; 7Aveleijn, Borne, the Netherlands; 8Novadic-Kentron, Vught, the Netherlands; 9Behavioral Science Institute, Radboud University, Nijmegen, the NetherlandsCorrespondence: Esther Pars, Department of Psychiatry, Radboud University Medical Center, PO Box 9101, Nijmegen, 6500 HB, the Netherlands, Tel +31 24 361 35 13, Email Esther.Pars-vanWeeterloo@radboudumc.nlPurpose: Substance use disorder (SUD) can be a chronic relapsing condition with poor treatment outcomes. Studies exploring factors associated with abstinence or relapse after treatment are often quantitative in nature, applying linear statistical approaches, while abstinence and relapse result from non-linear, complex, dynamic and synergistic processes. This study aims to explore these underlying dynamics using qualitative comparative analysis (QCA) as a mixed methods approach to further our understanding of factors contributing to post-treatment abstinence and relapse.Patients and Methods: In a prospective study, we gathered both qualitative and quantitative data pertaining to post-treatment substance use and the factors linked to substance use outcomes. These factors encompassed psychiatric comorbidity, intellectual disability, social disintegration, post-treatment support, and engagement in activities among patients who had undergone inpatient treatment for severe SUD (n = 58). QCA, a set-theoretic approach that considers the complex interplay of multiple conditions, was applied to discern which factors were necessary or sufficient for the occurrence of either abstinence or relapse.Results: We found two solutions predicting abstinence, and five for relapse. Post-treatment conditions (support and engagement in activities) were important for retaining abstinence. For relapse, individual baseline characteristics (intellectual disability, social disintegration, psychiatric comorbidity) combined with (post-)treatment factors (post-treatment support, activities) were important.Conclusion: Although abstinence and relapse represent opposing outcomes, they each exhibit distinct dynamics. To gain a comprehensive understanding of these dynamics, it is advisable to examine them as separate outcomes. For clinical practice, it can be worthwhile to recognize that fostering the conditions conducive to abstinence may differ from preventing the factors that trigger relapse.Plain Language Summary: This study explores why some people who struggle with addiction stay clean after treatment, while others relapse. Previous studies often used traditional statistical methods, with inconclusive results due to their inability to capture the complexity of this process. To address this, we used a different approach called qualitative comparative analysis (QCA).We collected information from 58 individuals who received inpatient treatment for their addiction. We looked at different factors like mental health problems, intellectual disability, the support they got from professionals and their social network, and whether they kept themselves busy with activities. We investigated how these factors are related to staying clean or relapse. With the help of QCA, we analyzed how these factors work together to cause either drug-free living or relapse.We found that staying clean was strongly linked to getting support after treatment and being involved in activities like hobbies or work. On the other hand, relapse was more likely in people with personal problems, like intellectual disabilities and mental health problems, when support and activities were lacking after treatment.In summary, our study indicates that staying clean and relapse are different processes with different factors at play. Helping someone stay clean may therefore require different strategies than preventing relapse. This insight can guide development of more personalized healthcare for individuals dealing with addiction.Keywords: addiction, substance use outcomes, qualitative comparative analysis